Optimizing Service Quality: Exploring the Impact of Service Excellence and Service with Care, Mediated by Community Culture - Arieanti, Dian Dinarafika; Rismawati, Rismawati; Suparti, Suparti (Mahameru Publisher, 2023)
This study aims to analyze the effect of Service Excellent and Service with Care on Service Quality at RSI Garam Kalianget. In addition, this study also aims to examine the effect of Service Excellent and Service with Care on Community Culture at RSI Garam Kalianget. This study used a quantitative approach with a sample of 120 respondents from urban, rural and island areas. The results of the study show that Service Excellent and Service with Care have a positive and significant impact on Service Quality. In addition, Service Excellent also has a positive and significant impact on Community Culture, as well as Service with Care. These results indicate that the implementation of superior service and attention to customer care simultaneously contribute to improving service quality in this hospital, and Community Culture acts as a mediating variable that influences the relationship between service and service quality. This research contributes by expanding understanding of the factors that play a role in improving service quality and the role of community culture as an important mediator in this relationship.